2018
DOI: 10.1007/s00410-018-1528-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep pre-eruptive storage of silicic magmas feeding Plinian and dome-forming eruptions of central and northern Dominica (Lesser Antilles) inferred from volatile contents of melt inclusions

Abstract: Volatiles contribute to magma ascent through the sub-volcanic plumbing system. Here, we investigate melt inclusion compositions in terms of major and trace elements, as well as volatiles (H 2 O, CO 2 , SO 2 , F, Cl, Br, S) for Quaternary Plinian and dome-forming dacite and andesite eruptions in the central and the northern part of Dominica (Lesser Antilles arc). Melt inclusions, hosted in orthopyroxene, clinopyroxene and plagioclase are consistently rhyolitic. Post-entrapment crystallisation effects are limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 65 publications
(106 reference statements)
4
38
0
Order By: Relevance
“…The mineralogy of the magma emitted during the four eruptions is very similar, and similar to that of the ignimbrites (Balcone‐Boissard et al, 2018): In decreasing order of abundance, PLAG, OPX, CPX, and MGT are present as phenocrysts in the magmas. Their composition is given in Table S2.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The mineralogy of the magma emitted during the four eruptions is very similar, and similar to that of the ignimbrites (Balcone‐Boissard et al, 2018): In decreasing order of abundance, PLAG, OPX, CPX, and MGT are present as phenocrysts in the magmas. Their composition is given in Table S2.…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, some melt inclusions contain high CO 2 concentrations (3,000 to 4,000 ppm) but comparatively low H 2 O concentrations (<2.7 wt%) and therefore very low H 2 O/(H 2 O + CO 2 ) ratios. Balcone‐Boissard et al (2018) also observed such high CO 2 contents in melt inclusions from MTPM ignimbrites. Caricchi et al (2018) attributed this phenomenon to CO 2 flushing from deep levels within the magma plumbing system, driving melt dehydration and crystallization at shallower levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high water contents recorded in Statia MIs (0.1–9.1 wt% H 2 O) are consistent with high water contents measured in melt inclusions from Montserrat (Humphreys et al 2009 ; Cassidy et al 2015 ), Bequia (Camejo-Harry et al 2018 ) and Dominica (Balcone-Boissard et al 2018 ) up to 6.2, 7.8 and 8 wt% H 2 O, respectively. In addition, independent estimates of melt water contents using orthopyroxene in andesites from Soufrière Hills Volcano, Montserrat, suggest melt water concentrations of 6–9 wt% H 2 O (Edmonds et al 2016 ).…”
Section: Discussionsupporting
confidence: 79%
“…The phase compositions for the natural samples are given in Table 2. The water contents of the experimental residual glasses were determined following the by-difference method using the EMP analyses and the glass standards in Balcone-Boissard et al (2018). Phase proportions of the experimental charges were obtained by mass-balance calculations and compared to those obtained on natural samples by Boudon et al (2017).…”
Section: Sample Analysismentioning
confidence: 99%